South East Europe and Maternal Mortality - Beksaç, Sinan; Adamova, Gordana; Antolic, Ziva Novac; Crnogorac, Sneezena; Gliozheni, Orion; Koç, Acar; Mazneikova, Valentina; Moisiu, Rubena; Motrenko, Tatjana; Onofriescu, Mircea; Özyüncü, Özgür; Pavlova, Kamelia; et al. (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: Maternal mortality has always been thought as one of the primary indicator of developmental status of a country. There may be some problems in achieving this level. Almost all of the south east European countries are developing countries and share some similarities regarding the social, cultural and economical background. Thus, incidence and etiologies of maternal mortality and therefore precautions are thought to be similar. To determine the current status we decided to make a survey with the related countries within the context of 2nd Congress of SEESPM. This report will summarize the results of the attendant countries. STUDY DESING: A simple questionnaire related to maternal mortality was prepared asked each representative to fill that form. The questionnaire consisted of three parts. Aim of the first part was to get some knowledge about the geographical and economical properties of that country The second part was related directly to maternal mortality. The third part was about the etiology of maternal mortality. RESULTS: Turkey has the largest surface area and the largest population among the countries. But Romania has the largest gross domestic product and the mean gross national income per capita. Most of the countries have national legislations for maternal mortality, presence of skilled attendant in delivery and for abortions. Among the countries Albania has the highest maternal mortality rate. All the attendant countries have national registry for maternal mortality and therefore these data belong to nationwide statistics in all of the countries.